ТHE VERBAL ADVERB AND ITS EQUIVALENTS IN ENGISH (Philological Studies, 2022)
The aim of this paper is to give an outline of the verbal adverb in Macedonian and its translation equivalents in Macedonian. Therefore, an exception of the corpus of sentences of Macedonian works translated into English has been analyzed. When analyzing the excerpted corpus of sentences, a classification of three groups has been made. Namely, the largest group is the first group where the verbal adverb is translated as a present participle in English and there is a dual match regarding the form and the semantic meaning. The second group is divided into a few subgroups concerning the translation equivalent of the verbal adverb. In this group, there is a semantic match especially when the verbal adverb is translated with a finite verbal form. Additionally, besides the finite verb forms, there are prepositional phrases, adjectives, and adverbs as English translation equivalents. The third group is comprised of excerpted examples where there is a complete mismatch, i.e., the verbal adverb is omitted in the English translation equivalent.